Chromosomal aberrations in 130 patients with multiple myeloma studied by interphase FISH: diagnostic and prognostic relevance - Schmidt-Wolf, Ingo G.H.; Glasmacher, A.; Hahn-Ast, C.; Jüttner, A.; Schnurr, T.; Cremer, Friedrich Walter; Möhler, Thomas; Goldschmidt, Hartmut; Busert, B.; Schubert, R.; Schwanitz, G. (Cancer genetics and cytogenetics, 2006)
The study described the molecular cytogenetic characterization of myeloma cells in 130 patients via interphase fluorescence in situ hybridization. Nine repetitive DNA probes (for chromosomes 3, 7, 9, 11, 15, 17, 18, X, and Y) as well as seven single-copy DNA probes (for chromosomes 13, 17, 21, and two each for chromosomes 5 and 22) were used for the hybridizations. Using this panel of probes, we were able to show aberrations in 86% of patients. Most of them had one to three aberrations. There was a distinct correlation between the number of aberrations per patient and the tumor stage. Thus, the proportion of patients with 8-12 aberrations increased from 16% in stage II to 26% in stage III. There were marked differences among the chromosomes with respect to the prevalence of genomic losses and gains and deletions of gene loci. Chromosomes 3, 5, 7, 9, 11, 15, and 21 showed a preference for genomic gains. Losses were most often found for chromosomes 13 and 17 (locus specific) as well as for the X and Y chromosomes. The frequency of monosomies and trisomies were approximately the same for chromosomes 15 and 18, which indicates a skewed pattern of distribution. We found two specific aberrations that caused distinct changes in the survival rates of the patients: deletion 13q14 (28% of patients) and translocation of the IGH locus 14q32 (79% of 39 patients who were analyzed separately). The results obtained in this study yielded data of extremely relevant prognostic value.
Gesehen am 15.02.2022